Faktor-Faktor Derteminan Daya Saing Kontraktor Konstruksi di Sumatera Barat - Ilyas, Budi; Jumas, Dwifitra; Rita, Eva (Jurnal Ilmiah Rekayasa Sipil, 2025)
The competitiveness of contractors plays a crucial role in supporting the successful implementation of infrastructure development programs, particularly in regions such as West Sumatra where both central and local government projects are intensively carried out. This study aims to identify and analyze the main factors influencing contractor competitiveness in West Sumatra. A quantitative research design was adopted, utilizing a structured questionnaire distributed to contractors, consultants, electronic procurement services (LPSE), and users of contractor services, with a total of 121 valid responses. From an extensive literature review, 53 variables were identified, which were subsequently reduced to 22 relevant variables. Exploratory Factor Analysis (EFA) was conducted, followed by Horn Parallel Analysis (HPA) to confirm factor validity. The results indicate that 16 variables significantly influence competitiveness and can be grouped into three major factor constructs: (1) Resource Factors, (2) Marketing and Relationship Factors, and (3) Management and Strategy Factors. Further evaluation using Measurement Model Analysis (MMA) with Smart PLS confirmed the convergent and discriminant validity of the constructs, demonstrating that these three factors have a direct impact on contractor competitiveness. The ranking analysis highlights financial capacity, human resources, government relations, organizational structure, and technology as the most critical elements. The findings provide theoretical contributions by strengthening the conceptual understanding of competitiveness factors in the construction sector and practical implications for contractors in West Sumatra to enhance their strategies in a highly competitive environment. Moreover, improving local contractors’ competitiveness will contribute to increasing national construction competitiveness.